Cascade plasmapheresis as a desensitization strategy for patients undergoing ABO incompatible living donor liver transplantation (ABOi LDLT): A single center experience. (August 2019) - Bajpai, Meenu; Kakkar, Brinda; Gupta, Shruti; Rastogi, Archana; Pamecha, Viniyendra
Abstract: Background and aim: The reduction of antibody titres (AT's) to a safe level is essential pre-requisite for patients awaiting ABO-incompatible liver transplantation (ABOi LT). We report our experience of performing cascade plasmapheresis (CP) on 2 different apheresis platforms (COBE Spectra and Spectra Optia) as a desensitization strategy for patients undergoing ABOi LT in our centre. Methods: This retrospective observational study was conducted on patients who underwent CP included in the desensitization protocol for ABOi LDLT. CP/conventional TPE was performed (daily/alternate day with daily estimation of AT) until a target titre of ≤ 8 was achieved. Results: During the study period, 4 patients (mean age 46.7 years; 100% males) underwent desensitization for ABOi LDLT with baseline AT (combined IgM and IgG) ranging from 64 to 512. A total of 15 CP sessions (range 2 - 6) were performed with a median of 3.5 sessions/patient. Desensitization rate was 100%. Only 1 patient underwent conventional TPE in the post-transplant due to rise in AT level to 64 (post-operative day 8). Average post-operative length of stay was 49 days (range 30 - 105). None of the patients experienced any episode of rejection (repeat liver biopsy). On follow up (1 year), 2 patients were alive and doing well, while other 2 patients succumbed during their hospital stay due to sepsis. Conclusion: In our limited experience, the use of CP was safe and effective desensitization strategy for patients undergoing ABOi LDLT.